The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s1516-18462006000400006
|View full text |Cite
|
Sign up to set email alerts
|

Disfunções orofaciais nos pacientes em tratamento ortodôntico

Abstract: Purpose: to evaluate the need for speech therapy intervention in patients treated in the orthodontic clinic of the Federal University of Juiz de Fora. Methods: clinical examinations, application of questionnaire and clinical medical register analysis of 42 patients under orthodontic treatment in the Federal University of Juiz de Fora had been carried out. The first phase of this study was made up by the evaluation of the habitual tongue position, breathing function, deglutition and speech. Soon afterwards, dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
15

Year Published

2014
2014
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 5 publications
0
7
0
15
Order By: Relevance
“…Findings agree with studies of Cavalcanti and Bianchini 16 and Duarte 17 , who also found no significant correlation between occlusion and the preferred chewing side. However, is quoted in the literature the influence of occlusal factors in masticatory pattern mainly involving the unilateral occlusal pattern with changes and temporomandibular dysfunction 18,19 . When analyzed the chewing pattern and occlusion type, for the studied sample, there was no relationship between the variables (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Findings agree with studies of Cavalcanti and Bianchini 16 and Duarte 17 , who also found no significant correlation between occlusion and the preferred chewing side. However, is quoted in the literature the influence of occlusal factors in masticatory pattern mainly involving the unilateral occlusal pattern with changes and temporomandibular dysfunction 18,19 . When analyzed the chewing pattern and occlusion type, for the studied sample, there was no relationship between the variables (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…This system is responsible for sucking, chewing, swallowing, breathing and speech functions [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…Aspects such as strength, time and type of mastication can be affected by changes in proprioception 13 , and changes in neuromuscular coordination may lead to mastication and deglutition disorders 7,14 .…”
mentioning
confidence: 99%